Implementation of Greening, Local Ecotourism, and Drip Irrigation Programs to Increase Environmental Awareness in Durian Village - Gilang Cahya; Putri Nurul Khalifah; Amanda Maharani; Resti Aulia Lestari; Ida Ayu Indira Prameswari; Sahrul Gunawan; Ida Apriani; Muhammad Haris Satyawan Rahman; Miftahul Jannah (Yayasan Siti Widhatul Faeha, 2026)
Durian Village in Janapria District possesses considerable natural resource potential; however, its management and utilization have not yet been optimized to support sustainable development. Therefore, this program aimed to support sustainable village development through the integration of greening initiatives, ecotourism development, and water conservation education implemented through the Community Empowerment Village Fieldwork Program (CEVFP), locally known as Kuliah Kerja Nyata (KKN), of the University of Mataram. The program applied a participatory approach involving observation, interviews, community socialization, and direct collaboration with residents and village authorities. The activities included planting seedlings and trees in strategic village areas, mapping and initial arrangement of locations with potential to become ecotourism destinations, and providing counseling accompanied by simple demonstrations of drip irrigation technology to promote water-use efficiency. The results showed an increase in community awareness of environmental conservation, growing public participation in maintaining planted vegetation, and emerging interest in developing nature-based tourism potential. In addition, the drip irrigation education provided new insights for farmer groups regarding efficient water use and opportunities to improve agricultural productivity, particularly during the dry season. Overall, the Community Empowerment Village Fieldwork Program (CEVFP/KKN) generated positive ecological and socio-economic impacts on the community. These findings highlight the importance of participatory community-based development models in supporting sustainable village development and emphasize the need for continued assistance, strengthening of village institutions, and collaboration among stakeholders to ensure program sustainability